'Patient-Empowerment Programme' against standard care in advanced heart failure patients – a randomised controlled trial / Mohd Zhafran Zainal Abidin - Zainal Abidin, Mohd Zhafran (2017)
Introduction: Progressive Muscle Relaxation Therapy (PMRT) and Energy conservation technique (ECT) has been used among chronic illness patients to reduce symptoms burden and improve quality of life. However, data regarding these therapies among advanced heart failure patients remain limited. This study aimed to evaluate the effects of PMRT and ECT on functional capacity, symptoms assessment scores and quality of life amongst advanced heart failure patients. Methods: This was a 12-week, two-arm, parallel, non-blinded, randomized control trial in a single centre. The study compared 42 patients receiving standard care (SC) against 48 patients receiving "Patient-Empowerment Programme (PEP)" (SC+PMRT+ECT). 90 advanced heart failure patients were enrolled. The intervention group received two PEP reinforcement sessions four weeks apart. Patients were asked to implement the programme at least three times a week at home, using an audio-visual aid. Assessment tools comprised of questionnaires on demographics, 6-minute walking test (6MWT), New York Heart Association (NYHA) classifications, Revised version of the Edmonton Symptoms Assessment System (ESAS-r), Brief Fatigue Inventory (BFI), New York Heart Association (NYHA) Classification and McGill Quality-of-Life Questionnaire (MQOL-R) administered on recruitment and upon study completion. Result: 76 (84.4%) were male. Mean age was 59.93 years (+ 11.16) and majority was from the lower income group. There was a 11.99m (95%CI: 5.99, 15.98) (p <0.05) improvement in the 6MWT between intervention and standard group. All symptoms showed improvement after intervention, however, only the depression and anxiety items were significant. There was improvement in the fatigue scale, factional status and quality of life in the intervention group however it is not statistically significant. Conclusion: ECT and PMRT are useful in reducing depression and anxiety scores, and improve the 6MWT distance. A larger sample size and longer study duration should be conducted to validate this result